2013
DOI: 10.3945/ajcn.112.055202
|View full text |Cite
|
Sign up to set email alerts
|

Sequential release of milk protein–derived bioactive peptides in the jejunum in healthy humans

Abstract: Background:The digestive hydrolysis of dietary proteins leads to the release of peptides in the intestinal tract, where they may exert a variety of functions, but their characterization and quantification are difficult. Objectives: We aimed to characterize and determine kinetics of the formation of peptides present in the jejunum of humans who ingested casein or whey proteins by using mass spectrometry and to look for and quantify bioactive peptides. Design: Subjects were equipped with a double-lumen nasogastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(195 citation statements)
references
References 47 publications
(64 reference statements)
11
158
0
11
Order By: Relevance
“…In general, the peptides which were predicted in silico to be released by GI enzymes (Table 2) have not been identified in the GIT (Table 3). However, 50 larger β-CN peptides predicted to be released in silico (Table 2) may act as precursors of the five β-CN derived W-containing peptides which has been identified in the jejunal contents of humans 32 . These peptide precursors may be further cleaved by carboxy-and aminopeptidases present in the GIT of humans 39,40 .…”
Section: Release Of Free W and W-containing Peptides During The Digesmentioning
confidence: 99%
“…In general, the peptides which were predicted in silico to be released by GI enzymes (Table 2) have not been identified in the GIT (Table 3). However, 50 larger β-CN peptides predicted to be released in silico (Table 2) may act as precursors of the five β-CN derived W-containing peptides which has been identified in the jejunal contents of humans 32 . These peptide precursors may be further cleaved by carboxy-and aminopeptidases present in the GIT of humans 39,40 .…”
Section: Release Of Free W and W-containing Peptides During The Digesmentioning
confidence: 99%
“…Por ejemplo, la mucosa gástrica de estos recién nacidos secreta niveles bajos de ácido clorhídrico, lo que posibilita que el pH gástri-co postprandial llegue a valores cercanos al neutro; el pH más alto disminuye la activación de la pepsina y la actividad antimicrobiana del jugo gástrico 28 . La mayor velocidad de vaciamiento de las proteínas parcialmente hidrolizadas es una ventaja porque permite el descenso del pH y el retorno de la actividad bactericida en el lumen gástrico 9,11 . La enteroquinasa es sintetizada por los enterocitos del duodeno y activa al tripsinógeno, el quimotripsinógeno y la proelastasa y a otras proteasas pancreáticas a sus formas activas 28 .…”
Section: Origen De Las Proteínas De La Leche Maternaunclassified
“…b) Milk and derivatives As a point of view, full or skimmed milk contains two major types of proteins: casein and whey proteins (milk without casein). It appears that whey proteins are faster (twice) rejected from the stomach into the duodenum as compared to casein [130][131][132][133] increasing therefore food availability during muscle exercise. As well, Burke et al observed that whey protein ingestion induced a faster inclusion within plasma volume as compared to whole milk [44].…”
Section: A) Classical Protein Feedingmentioning
confidence: 99%